ANALISIS SWOT DALAM PENGEMBANGAN MUTU PENDIDIKAN DI SMP NEGERI 6 SAMARINDA - Ambar Sri Pratiwi; Yasinta Monitasari; Alya Puspita Zahra; Hendra Putra Sastranegara; Pratisa Martha Sari; Zainal Pahmiyadi; Nurlaili; Usfandi Haryaka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Improving the quality of education needs schools to create plans that can change and grow as things inside and outside the school change. This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) in the development of SMP Negeri 6 Samarinda and to formulate appropriate school development strategies to improve educational quality. This research used a qualitative descriptive approach with SWOT analysis. The data collection process differs because it emphasizes that individual rights must be aligned with the principles of Pancasila. The data were gathered through interviews, observations, and documentation involving school principals, teachers, education staff, and school documents. The results showed that SMP Negeri 6 Samarinda has several strengths, such as experienced teachers, good learning facilities, and a supportive school environment. However, weaknesses were identified in the utilization of educational technology, disparities in students’ abilities, and limited infrastructure and budget. Opportunities include government support programs, technological advancements, and institutional partnerships, while threats consist of school competition, social media influence, economic conditions of parents, and dynamic educational policies. Based on the SWOT analysis, the school's development strategy should focus on making the most of its strengths and opportunities, while also working to reduce its weaknesses and threats. This can be done by improving the skills and knowledge of teachers, making the most of digital learning tools, focusing on teaching character education, and building better connections with all the people involved, like parents and the community. The study concludes that SWOT analysis offers a comprehensive foundation for strategic school development and sustainable improvement of educational quality. Keywords : Educational Quality, School Development Strategy, SWOT Analysis